(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2015)
This article discusses the concept of wali (guardian) with special focus on the discussion of the definition and categories of wali based on fiqh (Islamic jurisprudence) and legal perspectives in Malaysia. Critical comparison was made to the provisions of the Islamic Family Law of the states in Malaysia, focusing on interpretation and categorization of wali. Legal interpretation is essential to clarify the jurisdiction of wali and to facilitate judicial procedures in resolving cases related to validation or revocation of a marriage contract, or in the case of transfer of power of a wali. Undoubtedly, differences of opinion among fiqh jurists are the key element to the comprehensiveness of the Islamic shariah. However, aspects of the uniformity of legal provisions are a catalyst for ensuring that the shariah judicial system in Malaysia will be more effective and systematic. Keywords: shariah, wali, marriage, fiqh perspective, Islamic Family Law